Management in Efforts to Improve the Quality of Human Energy - Rosyidatul Azkiyah; Fina Kholij Zukhrufin; Chokchai Yuenyong (Jurnal Pendidikan Nusantara, 2024)
School or Madrasah Standard Management (MBSM) is an educational concept that strives to improve the quality, efficiency, and benefits in the education process through the active participation of the madrasah committee, teachers, students, parents, and the surrounding community as a form of support and full involvement in the education process. In implementing MBSM, all relevant parties such as the madrasah committee, school principal, teachers, students, parents, and the surrounding community can be involved to achieve sustainable educational goals. Through active cooperation from all parties, it is expected that the concept of MBSM can be achieved and provide significant benefits in the world of education, as well as advancing MA Muhammadiyah Tempurrejo Ngawi with an appropriate concept. Then, with the Total Quality Management (TQM) approach method at Lembaga Muhammadiyah in developing MBS to support independence and explore all potential that exists within the students themselves and this is one of the improvements of MA Muhammadiyah Tempurrejo Ngawi which has established dormitories (Al-Ihsan). Although the policy application is still less optimal, the active dormitory management tries to organize these policies with TQM to improve quality, improve dormitory programs, administrative services, and the emergence of teachers in active and effective leadership. This can help students achieve their full potential, create an innovative and comfortable learning environment, and contribute or socialize with the surrounding community of the dormitory.